Maru Samridhi: New lasora variety - Meghwal, P R; Singh, Akath (Indian Horticulture, 2019)
The lasora variety, Maru Samridhi has been released by Central Arid Zone Research Institute, Jodhpur recently. It is an improved high yielding variety with an averages fruit yield of 85 kg fruits/plant. Mean plant height and canopy diameter is 4.5 m and 7 m respectively. It is regular fruit bearer, and starts fruiting in third year of planting. Its flowering occurs during Feb-March and fruits mature during April-May. Average fruit weight is 10.5 g, edible part 84.61%, crude protein 11.06% (dry weight basis), crude fibre 13.4% (dry weight basis) and dry matter 15.37%.